2021
DOI: 10.1111/jasp.12831
|View full text |Cite
|
Sign up to set email alerts
|

Intergroup biologization and outgroup prejudice in the time of COVID‐19

Abstract: Through two studies ( N = 602) conducted in Italy between February and March 2020, we examined the impact of the COVID‐19 emergency on biologization—a form of dehumanization that involves the perception of others as contagious entities—and outgroup prejudice. Overall, results showed that higher emergency perception was associated with greater biologization toward the groups most affected by the virus, namely the Chinese outgroup and the Italian ingroup. In turn, biologization toward the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 77 publications
1
3
0
Order By: Relevance
“…Based on Singaporean data, Ahmed et al (2021) show how disease risk perception is related to stereotyping and discrimination against Chinese immigrants. Research conducted by Valtorta et al (2022) corroborates this finding using an Italian sample. According to Croucher et al (2020) , U.S. adults who use social media more frequently believe that Asian Americans (in particular, Chinese) pose both a symbolic and a realistic threat to their country.…”
Section: A Dual Theme In Prior Studiessupporting
confidence: 69%
“…Based on Singaporean data, Ahmed et al (2021) show how disease risk perception is related to stereotyping and discrimination against Chinese immigrants. Research conducted by Valtorta et al (2022) corroborates this finding using an Italian sample. According to Croucher et al (2020) , U.S. adults who use social media more frequently believe that Asian Americans (in particular, Chinese) pose both a symbolic and a realistic threat to their country.…”
Section: A Dual Theme In Prior Studiessupporting
confidence: 69%
“…Furthermore, our research highlights the difference between biologization and animalization, namely the only two forms of dehumanization implying representations of others as less-evolved living beings. Valtorta and Volpato (2018) deepened the analysis of this differentiation through an experimental study and showed that physical and moral disgust affect these two kinds of dehumanizing processes differently. They found that while physical disgust (i.e., a rejection response to dirt) increased the view of outgroup members as disease carriers, moral disgust (i.e., a form of disgust elicited by immorality and violations of social rules) led to an increased association of others with animalistic metaphors.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, one perspective that has, so far, been largely overlooked in the scientific literature is ingroup dehumanization, that is, the perception and treatment of one’s ingroup as less human than other groups. As far as we know, only a handful of pieces of research have considered this phenomenon; for example research by Valtorta and colleagues (2022) conducted in Italy during the COVID pandemic that found that Italian people biologically dehumanized their ingroup. Future research is needed to expand our knowledge about this phenomenon by integrating, for example, what is known about collective guilt (see Čehajić et al, 2009).…”
Section: Research Agendamentioning
confidence: 99%
“…Finally, recent models also referred to biologization, where dehumanization implies the association of human targets with viruses or diseases (Volpato & Andrighetto, 2015; see recent work by Valtorta et al, 2021, 2022), and to objectification, where the person or the group under consideration is considered as an object, a tool, or an instrument to be used by other people for their own ends. Interestingly, objectification has been shown to consist of a denial of both the two dimensions of humanness to the dehumanized target (e.g., Baldissarri, Andrighetto, et al, 2022).…”
mentioning
confidence: 99%